2021
DOI: 10.20944/preprints202111.0458.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-Dependent Decline of NAD+ - Universal Truth or Confounded Consensus?

Abstract: Nicotinamide adenine dinucleotide (NAD+) is an essential molecule involved in various metabolic reactions, acting as an electron donor in the electron transport chain and as a co-factor for NAD+-dependent enzymes. In the early 2000s, reports that NAD+ declines with aging introduced the notion that NAD+ metabolism is globally and progressively impaired with time. Since then, NAD+ became an attractive target for potential pharmacological therapies aiming to boost NAD+ levels to promote vitality and protect again… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 94 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Although promising as such, a recent review of studies on this topic concluded that despite overall claims of NAD + decline with age the scientific evidence is rather limited and often restricted to certain tissue types. Additionally, the authors highlight the potential selection bias attached to narrative literature reviews and shed light on the importance of unbiased longitudinal studies to establish an evidence‐based foundation for the abovementioned claims 30 . Hence, while the exact impact of aging on tissue NAD + content remains unclear (especially in humans), tissue‐specific alterations of NAD + homeostasis are frequently reported in disease settings, 31 making tissue‐specific approaches indispensable when investigating NAD + ‐modifying interventions.…”
Section: Nad+ Metabolism In Aging and Diseasementioning
confidence: 99%
“…Although promising as such, a recent review of studies on this topic concluded that despite overall claims of NAD + decline with age the scientific evidence is rather limited and often restricted to certain tissue types. Additionally, the authors highlight the potential selection bias attached to narrative literature reviews and shed light on the importance of unbiased longitudinal studies to establish an evidence‐based foundation for the abovementioned claims 30 . Hence, while the exact impact of aging on tissue NAD + content remains unclear (especially in humans), tissue‐specific alterations of NAD + homeostasis are frequently reported in disease settings, 31 making tissue‐specific approaches indispensable when investigating NAD + ‐modifying interventions.…”
Section: Nad+ Metabolism In Aging and Diseasementioning
confidence: 99%